Evaluation of Sensitization to Various Foods in a Subset of Subjects from Saudi Arabia - Alsaeed, A.H.; Harfi, H. Al; Shaik, A.P. (Pakistan Journal of Nutrition, 2013)
This study investigated sensitization to various foods in a subset of patients presenting to an allergy clinic with symptoms suggestive of a possible food allergy. A total of 243 subjects who visited the clinic were further screened and assessed for specific IgE antibodies to different food allergens by using the Radio Allergosorbent Test (RAST). IgE-antibodies specific for different foods were detected in 15.6% out of 243 patients. The maximum number of positive reactions were observed among these subjects to wheat (45%) followed by egg/egg white (40%), cow’s milk (39%), sesame seeds (35%) and soya bean (30%). Positive reactions were also found towards orange, rice, peanut, cashew nuts and dates. Most of the reactions fell in Class 2 followed by Class 3 and Class 1. These results are important and gave an idea of the most common food items to which allergic subjects were sensitized to. However, more studies are needed to gather data with respect to the various types of food allergy in the Saudi Arabian population for appropriate preventive measures to be put in place.